5u+5=-26u

Simple and best practice solution for 5u+5=-26u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5u+5=-26u equation:


Simplifying
5u + 5 = -26u

Reorder the terms:
5 + 5u = -26u

Solving
5 + 5u = -26u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '26u' to each side of the equation.
5 + 5u + 26u = -26u + 26u

Combine like terms: 5u + 26u = 31u
5 + 31u = -26u + 26u

Combine like terms: -26u + 26u = 0
5 + 31u = 0

Add '-5' to each side of the equation.
5 + -5 + 31u = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 31u = 0 + -5
31u = 0 + -5

Combine like terms: 0 + -5 = -5
31u = -5

Divide each side by '31'.
u = -0.1612903226

Simplifying
u = -0.1612903226

See similar equations:

| 3x-30=3x-9 | | (3r+8)=(r-4) | | n+6=9*5 | | 3x-30+6-15=3x-9 | | 3r^2-5r=-10 | | 2k^12+19k^6-33=0 | | n+5(2n+3)=37 | | 2x-4(x+1)=20 | | 6x+3=2x+18 | | 5u+5=26u | | -n-5(-6-7n)=-119 | | 25=7x-10 | | 8x+10=3x+15 | | 3y-3=5y-3 | | 2(x-3)+4x-(X+1)=3x+5(2x-3)-8 | | 2(10-5v)= | | 14-2x-16=5x-3x+34 | | 6(4z-2)=36 | | -40-8v=-5(1+3v) | | -7x-8y=-2 | | -39.6=12-0.4s | | 4x+9=-x+4 | | -17+16-x=16 | | 2y-x=y-5 | | 0.25+.05=6.10 | | 5b^2-22b-15=0 | | 18+8t=9(t-2) | | 3h-12=11h+4 | | 8(-9-2+3v-6v)= | | 2(4)-y=2 | | -6x-4(-7x-13)=58 | | 2(3)-y=2 |

Equations solver categories